2022
DOI: 10.1093/braincomms/fcac309
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid biomarkers for assessing Huntington disease onset and severity

Abstract: The identification of molecular biomarkers in CSF from individuals affected by Huntington disease may help improve predictions of disease-onset, better define disease progression, and could facilitate evaluation of potential therapies. The primary objective of our study was to investigate novel CSF protein candidates and replicate previously reported protein biomarker changes in CSF from Huntington disease mutation carriers and healthy controls. Our secondary objective was to compare the discriminatory potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 78 publications
(105 reference statements)
0
7
0
Order By: Relevance
“…In line with these data, an HD CSF biomarker exploration study showed unchanged expression of C1q subunits (C1qB and C1qC) across early-mid HD cohorts. 10 However, C1qB levels were substantially reduced in late-stage HD, which may reflect extreme loss of C1q-expressing neurons via phagocytosis as highlighted in the current study.…”
mentioning
confidence: 52%
“…In line with these data, an HD CSF biomarker exploration study showed unchanged expression of C1q subunits (C1qB and C1qC) across early-mid HD cohorts. 10 However, C1qB levels were substantially reduced in late-stage HD, which may reflect extreme loss of C1q-expressing neurons via phagocytosis as highlighted in the current study.…”
mentioning
confidence: 52%
“…NfL has emerged as a promising HD biomarker, with elevated CSF levels associated with disease severity and progression. Furthermore, NfL levels in plasma have been associated with disease progression and can predict the onset of the disease in premanifest mutation carriers [112].…”
Section: Huntington's Diseasementioning
confidence: 99%
“…Landmark studies in multiple neurodegenerative fields have repeatedly demonstrated shared impairments of neurotrophin homeostasis in human subjects and rodent models. These impairments most often include the regional downregulation of BDNF expression in affected neural structures [ 49 , 50 ] or in cerebrospinal fluid (CSF) vs. controls [ 51 , 52 , 53 , 54 ]. This downregulation is often associated with the dysregulation of transcription and translation of the BDNF gene, but it may also exist as a result of disruption of the proteolysis of its precursor, proBDNF, or through the altered metabolism of its mature isoform [ 54 , 55 ].…”
Section: Bdnf and Trkb-bdnf Signaling: Critical Intersections With Co...mentioning
confidence: 99%